2011
DOI: 10.1371/journal.pone.0020798
|View full text |Cite
|
Sign up to set email alerts
|

Superhelical Duplex Destabilization and the Recombination Position Effect

Abstract: The susceptibility to recombination of a plasmid inserted into a chromosome varies with its genomic position. This recombination position effect is known to correlate with the average G+C content of the flanking sequences. Here we propose that this effect could be mediated by changes in the susceptibility to superhelical duplex destabilization that would occur. We use standard nonparametric statistical tests, regression analysis and principal component analysis to identify statistically significant differences… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…High GC content is expected to potentially impact the frequencies at which recombination break points occur in various ways such as (1) predisposing genome regions to form stable secondary structures that could cause pausing of RNA-Dependent RNA polymerase (RdRP) ( Stark et al. 2006 ) ( Experimental Evidence Codes| BioGRID 2021 ), (2) increasing the energy needed to break base-pairs during replication, and increasing the amount of time taken for RdRP to traverse these regions ( Petes and Merker 2002 ; Sershen et al. 2011 ) and, if RdRPs disengages during replication, (3) increasing the probability of re-engagement through annealing with the same or a different template molecule ( Lai 1990 ).…”
Section: Resultsmentioning
confidence: 99%
“…High GC content is expected to potentially impact the frequencies at which recombination break points occur in various ways such as (1) predisposing genome regions to form stable secondary structures that could cause pausing of RNA-Dependent RNA polymerase (RdRP) ( Stark et al. 2006 ) ( Experimental Evidence Codes| BioGRID 2021 ), (2) increasing the energy needed to break base-pairs during replication, and increasing the amount of time taken for RdRP to traverse these regions ( Petes and Merker 2002 ; Sershen et al. 2011 ) and, if RdRPs disengages during replication, (3) increasing the probability of re-engagement through annealing with the same or a different template molecule ( Lai 1990 ).…”
Section: Resultsmentioning
confidence: 99%
“…Its susceptibility to recombine varies according to insertion site, and positively correlates with the G+C content of the flanking sequences. Calculations have shown that changing the base sequence in these flanks alters the predicted propensity to undergo superhelical strand separation at locations internal to the insert ( 84 ). This is a consequence of the long range coupling induced by superhelicity.…”
Section: Superhelical Transitions In Specific Biological Processesmentioning
confidence: 99%
“…calculated proportions of all nucleotide residues that were G or C between 10 or 20 nucleotide sites up and downstream of detected breakpoint locations). High GC content is expected to potentially impact the frequencies at which recombination breakpoints occur in various ways such as (1) predisposing genome regions to form stable secondary structures that could cause pausing of RNA-Dependent RNA polymerase (RdRP) (Stark et al 2006) (Experimental Evidence Codes | BioGRID 2021), ( 2) increasing the energy needed to break base-pairs during replication, and increasing the amount of time taken for RdRP to traverse these regions (Petes and Merker 2002;Sershen et al 2011) and, if RdRPs disengages during replication, (3) increasing the probability of re-engagement through annealing with the same or a different template molecule (Lai 1990).…”
Section: Breakpoints Tend To Fall At Sites With Lower Than Average Gc Contentmentioning
confidence: 99%